Filling the gaps: A community case study in using an interprofessional approach and community-academic partnerships to address COVID-19-related inequities - Kutchma, Marisa L.; Perez, Julianna; Stranges, Elizabeth; Steele, Kellie; Garis, Tayler; Prost, Anastazia; Siddiqui, Sumbul; Choo-Kang, Candice; Shaul, Bonnie; Benissan, Dede Golda Gbikpi; Smith-Haney, Gwendylon; Mora, Nallely; et al. (Frontiers in Public Health, 2023)
Public health challenges rapidly escalated during the COVID-19 pandemic. In response to a severe lack of resources and support in the near western suburbs of Chicago, the COVID Equity Response Collaborative: Loyola (CERCL) was established by an interprofessional team of Loyola University Chicago students, staff, and faculty. CERCL sought to minimize the negative impact of COVID-19 on vulnerable communities, those that are largely Black, Hispanic, or low-income. From April 2020 to the present, the collaborative utilized community-academic partnerships and interdisciplinary collaborations to conduct programming. CERCL’s programming included free community-based testing, screening for and assistance with social determinants of health, dissemination of relevant and reliable COVID-related information, provision of personal protective equipment, and facilitation of access to vaccines. With partners, the collaborative conducted 1,500 COVID-19 tests, trained 80 individuals in contact tracing, provided over 100 individuals with specifically tailored resources to address social and legal needs, distributed 5,000 resource bags, held 20 community conversations, canvassed 3,735 homes, and hosted 19 vaccine clinics. Community-academic partnerships with the health system, community and governmental agencies, and the local public health department have been critical to CERCL efforts. The interdisciplinary and interprofessional successes demonstrated in this case study lends the example of a relevant, sustainable, and practical intervention to address nuanced public health issues.